2006
DOI: 10.1042/bj20060578
|View full text |Cite
|
Sign up to set email alerts
|

Role of nucleotides and phosphoinositides in the stability of electron and proton currents associated with the phagocytic NADPH oxidase

Abstract: The phagocytic NADPH oxidase (phox) moves electrons across cell membranes to kill microbes. The activity of this lethal enzyme is tightly regulated, but the mechanisms that control phox inactivation are poorly understood for lack of appropriate assays. The phox generates measurable electron currents, I(e), that are associated with inward proton currents, I(H). To study the inactivation of the phox and of its associated proton channel, we determined which soluble factors can stabilize I(e) (induced by the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The enhanced gating mode was preserved only by a combination of 5 mM ATP, 50 µM ATPγ-s, and 25 mM phosphoinositide 3,4-bisphosphate [152]. Under similar conditions, we do not consistently observe rundown; however, it may be that our excised patches include submembrane components that preserve function.…”
Section: Biochemical Regulation Of Proton Channelsmentioning
confidence: 70%
See 1 more Smart Citation
“…The enhanced gating mode was preserved only by a combination of 5 mM ATP, 50 µM ATPγ-s, and 25 mM phosphoinositide 3,4-bisphosphate [152]. Under similar conditions, we do not consistently observe rundown; however, it may be that our excised patches include submembrane components that preserve function.…”
Section: Biochemical Regulation Of Proton Channelsmentioning
confidence: 70%
“…The “activated” state of proton currents, which is discussed below, was reported to exhibit rapid spontaneous rundown ( i.e ., reversion to the “resting” state) in excised inside-out membrane patches from eosinophils [57, 152]. The enhanced gating mode was preserved only by a combination of 5 mM ATP, 50 µM ATPγ-s, and 25 mM phosphoinositide 3,4-bisphosphate [152].…”
Section: Biochemical Regulation Of Proton Channelsmentioning
confidence: 99%
“…The current-voltage relationship of control neutrophils was outwardly rectifying with a threshold of activation around 30 mV, whereas the I-V curve of VSOP/Hv1 / neutrophils was completely flat. We and others previously suggested that the phagocyte NADPH oxidase contains a built-in proton channel (Henderson et al, 1987) that opens only when the oxidase is active (Bánfi et al, 1999;Petheo et al, 2006). Whether the oxidase is a proton channel or modulates another channel has been much debated (Maturana et al, 2002;Morgan et al, 2002;Touret and Grinstein, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The stability of the enhanced gating mode of proton channels in inside‐out patches appears to be supported by a combination of ATP, GTPγS and PI(3,4)P 2 (phosphoinositide 3,4‐bisphosphate). The mechanism was hypothesized to include interaction with the p47 phox component of NADPH oxidase (Petheö et al 2006), adding to the intriguing question of the nature of the relationship between proton channels and NADPH oxidase. The details of the interactions of these regulatory molecules with proton channels need further clarification.…”
mentioning
confidence: 99%